Established, accelerated and emergent themes in flexible work research. (April 2017) - Bessa, Ioulia; Tomlinson, Jennifer
Flexible labour markets, flexible working arrangements and motivations behind their use are established and expanding strands of sociology of work and employment relations research. This article provides a review of key themes and debates connected to workplace flexibility between 2000 and 2015 utilising research located in leading sociology of work, employment relations, industrial relations and human resource management (HRM) journals, in addition to key texts published during this time period. We establish that flexible work research is a growing area of research and focus our analysis on identifying key themes categorised as established, accelerated and emergent. We conclude with areas of contention yet to be resolved and possible avenues for future directions in flexible work research, noting a disconnection between macro analyses of flexibility at the economic level and the focus on flexible working-time arrangements at the workplace level. Furthermore we observed few quantitative multi-level modelling analyses or multi-methods research designs. To that end, analyses that can synthesise these literatures would enhance the field, as might innovations in methodological approaches which advance multi-level modelling and multi-method designs to give multiple and dynamic perspectives.